Moving Photocarrier Grating Technique for Mobility and Lifetime Measurements in Amorphous Semiconductors - Hundhausen, Martin; Ley, Lothar; et al. (Materials Research Society Symposium - Proceedings, 1994)
In this paper we describe a new method for the determination of the carrier lifetime (τ) and the carrier mobilities (μn, μp) in semiconductors. This technique utilizes a moving intensity grating that is generated by superposition of frequency shifted laser beams for the illumination of the sample. The material parameters are extracted from the short circuit current in the sample induced by the moving grating as a function of it's velocity (υgr). We solve the continuity equations and Poisson's equation in the small signal approach for the modulated electron and hole densities and show how these densities result in an electric field that in turn acts on the electrons and holes in order to yield a short circuit current density jsc. Erom a fit of this expression for jsc to experimental data we determine μn, μp and T. © 1994 Materials Research Society.
UnivIS-Import:2015-03-05:Pub.1994.nat.dphy.IAP.exphys.moving